Effects of water activity, temperature and particle size on thermal inactivation of Escherichiacoli ATCC 25922 in red pepper powder. (January 2020) - Zhang, Beihua; Zhang, Lihui; Cheng, Teng; Guan, Xiangyu; Wang, Shaojin
Abstract: Contaminated condiments with low water activity ( a w ) have encouraged the scientific community to study effective thermal methods of inactivating pathogens. The aim of this study was to identify whether microbial thermo-tolerance in red pepper powder was affected by water activity, treatment temperature and particle size of samples. Effects of three bacterial strains and particle size on the heat resistance were analyzed based on the orthogonal experiment method. Samples with particle size ranging from 0.45 to 1.00 mm and the most thermal resistance bacterial strain of Escherichia coli ATCC 25922 after comparing with two salmonella strains were chosen to study thermal inactivation kinetics in red pepper powder at three a w levels with four temperatures. The results indicated an increase of microbial thermal resistance with increasing mean particle sizes of red pepper powder. Logarithmic microbial inactivation was fitted by primary models in which the lower a w and temperature resulted in larger D -values. Mafart's modified Bigelow model combined with primary models provided acceptable predictions of microbial inactivation performance under the given test conditions. When a w levels were higher, E. coli ATCC 25922 was easier to kill at relatively lower temperatures. These findings may assist pepper powder manufacturers and regulatory agencies in designing effective pasteurization processes to ensure product safety. Highlights: Bacterial strains and sample particle sizes were determined by orthogonal tests. Large sample particle size and low a w level raised microbial thermal resistance. Microbial death data were well fitted by first-order kinetic and Weibull models. Modified Bigelow model improved microbial inactivation prediction.